ANALISIS KINERJA RUAS JALAN TERHADAP PASAR TRADISIONAL - Putri Endah Suwarni (Fakultas Teknik Universitas Tulang Bawang Lampung, 2017)
Way kandis market is one of the market center in marketing area in Bandar Lampung City whichhas the highestactyvity especially in busy tie, the problem is about the traffic flow conflictwhich causes traffic jam. This research aims to know about the condition of road capacity in Ratu dibalau street to the influence of the market activity in Way kandis market bby evaluating the influenceof the obstruction factor with the analysis ofcounting such the vehicles volume, the speed of vehicles and the road capacity based on the result of the surveying in the area so that it can solve the problemswhich happen in that area. Based on discution result from MKJI 1997 counting, it got the value of satitation degree in Ratu dibalau street in front of way kandis market is about 0,64 with the speed of vehicles is about 32 km/hr and includes to the highest obstructions factor. This is show thet Ratu dibalau in from of the way kandis market has a problem which causes the traffic jam with the time of speed is about 11,25 / second, this is from the problems which influence to the walker and vehicles park or stop. Keywords: road performance, traditional market, way kandis